Ureteric reimplantation via vaginal route: a new surgical technique. Issue 8 (14th August 2019) - Toia, Bogdan; Ockrim, Jeremy J; Greenwell, Tamsin J
Abstract: Vesicovaginal fistulae (VVF) and ureteric reimplantation are two rare complications of obstetric surgery. VVF can be repaired via a vaginal approach utilizing Martius fat pad interposition to minimize urethral complications and improve surgical outcomes, while ureteric reimplantation into the bladder classically necessitates an abdominal or laparoscopic approach. We present a new technique of ureteric reimplantation via vaginal approach with concomitant repair of a 5-cm VVF in a 25-year-old woman after an emergency caesarean section with bladder injury and ureteric transection. Good drainage was confirmed on MAG3 and successful vaginal birth (albeit preterm) was subsequently achieved.